Alu repetitive sequence CpG methylation changes in burn scars. Issue 6 (September 2022) - Meevassana, Jiraroch; Serirodom, Siwat; Prabsattru, Piyawan; Boonsongserm, Papatson; Kamolratanakul, Supitcha; Siritientong, Tippawan; Mutirangura, Apiwat; Angspatt, Apichai
Highlights: Alu methylation levels in burn scar tissues lower than in normal skin. Alu methylation levels higher in blood samples for burn scar patients. u C u C and u C m C patterns useful as markers with high sensitivity and specificity. Abstract: Alu elements are retrotransposons related to epigenetic modifications. To date, the role of epigenetics in hypertrophic scars from burn remains unknown. Here, our aim was to examine the pathophysiology of hypertrophic scars from an epigenetic perspective. For that, we performed a cross-sectional analytical study using tissue and blood samples from burned and healthy patients (n = 23 each) to detect Alu methylation levels and patterns. The results of the combined bisulfite restriction analysis technique were categorized into four groups based on the methylation status at the CpG dinucleotides from the 5′ to the 3′ ends of the Alu sequence: hypermethylated ( m C m C), hypomethylated ( u C u C), and partially methylated ( u C m C and m C u C). Alu methylation levels were significantly lower in hypertrophic scar tissues than in normal skin (29.37 ± 2.49% vs. 35.56 ± 3.18%, p = 0.0002). In contrast, the levels were significantly higher in white blood cells from blood samples of burned patients than in those of control blood samples (26.92 ± 4.04% vs. 24.58 ± 3.34%, p = 0.0278). Alu total methylation ( m C) and the u C m C pattern were significantly lower, whereas u C u C was significantly higher, in hypertrophic scar tissues than in normal skin (p < 0.0001). Receiver operating characteristic analysis indicated that the u C m C and u C u C patterns are useful as hypertrophic scar DNA methylation markers after burn, with 91.30% sensitivity and 96.23% specificity and 100% sensitivity and 94.23% specificity, respectively. Our findings suggest that epigenetic modifications play a major role in hypertrophic scar pathogenesis, and may be the starting point for developing a novel technique for burn scar treatment.